Gradient collagen hydroxyapatite conductive hydrogel and preparation method thereof
By adopting a dual crosslinking network structure and gradient distribution of hydroxyapatite in osteocartilage repair hydrogel, combining free moving metal ions and the Hoffmeister effect, the difficulty of existing hydrogels to form native tissues is solved. Similar structures and lack of conductivity have achieved efficient osteocartilage repair.
Patent Information
- Application Number
- CN202411601994.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-07
AI Technical Summary
Existing osteocartilage repair hydrogels are difficult to form osteocartilage structures similar to native tissues, and lack electrical conductivity and appropriate mechanical properties to adapt to the physiological environment of cartilage.
Gradient collagen hydroxyapatite conductive hydrogel using a dual crosslinking network structure forms a primary crosslinking network scaffold through collagen, sodium alginate, and polyvinyl alcohol, and secondary crosslinking through sodium alginate and metal ions. The network scaffold, hydroxyapatite, is distributed in a gradient manner, combining free moving metal ions and hydrophilic anions to improve mechanical properties and electrical conductivity.
The stability and mechanical properties of the hydrogel scaffold are improved, and the gradient distribution of mineral content during the transition from cartilage to subchondral bone is simulated, which enhances the binding ability with native tissues, and has excellent mechanical properties and conductive properties. Suitable for osteocartilage repair.
Smart Images

Figure CN119386272A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical engineering, and in particular relates to a gradient collagen hydroxyapatite conductive hydrogel and a preparation method thereof. Background Art
[0002] Osteochondral tissue consists of articular cartilage and subchondral bone, showing layered cell types, composition and matrix organization throughout its depth, combining the biomedical functions of lubrication, load bearing and shear transfer for body movement. Articular cartilage is a typical interface tissue. Articular cartilage defects can lead to exposure of subchondral bone, resulting in full-thickness osteochondral defect trauma or osteoarthritis, which is usually difficult to repair. The difficulty of repairing articular cartilage and subchondral bone lies in the continuous gradient construction and multiple levels of connective tissue, including the gradient construction of biological and physicochemical components (such as collagen, mechanical strength, inorganic mineral components, etc.).
[0003] Collagen is the main component of human connective tissue (such as cartilage, ligaments, tendons, skin, etc.). It is a spiral fibrous protein twisted from three peptide chains. It has the advantages of good biocompatibility, no toxic side effects, and can be degraded and absorbed. In particular, collagen extracted from the Achilles tendon of mammals by acid extraction and enzyme extraction retains a complete triple helix structure and has high mechanical strength. It can play a role in repairing cartilage and reducing friction, buffering and wearing resistance in the construction of osteochondral repair hydrogel. Hydroxyapatite is a calcium phosphate mineral that can induce bone formation and construct the mineral structure and mechanical strength of the gradient hydrogel.
[0004] In recent years, there are three main types of osteochondrocyte repair hydrogels: uniform osteochondrocyte repair hydrogels may have the ability to repair bone or cartilage, but this uniform structure may cause disorder in the repair process and make it difficult to form an osteochondrocyte structure similar to the native tissue; multiple hydrogels implanted in sequence may cause the material to break or deform in long-term tissue regeneration due to weak interface bonding and insufficient stability between the two layers; integrated multiphase osteochondrocyte repair hydrogels can form a bone-cartilage-like structure to meet the required biomedical functions at different depths. At present, the requirements for integrated multiphase osteochondrocyte repair hydrogels are that they have certain electrical conductivity to stimulate cell activity, certain mechanical properties and appropriate swelling rate to adapt to the physiological environment of cartilage, but the existing technology rarely combines functional gradients and morphological gradients in bone defect repair hydrogels.
[0005] Based on this, the present invention is proposed. Summary of the invention
[0006] The present application provides a gradient collagen hydroxyapatite conductive hydrogel and a preparation method thereof, which combines functional gradient (having electrical properties to stimulate cell activity) and morphological gradient (satisfying certain mechanical properties and appropriate swelling rate to adapt to the physiological environment of cartilage), while simulating the gradient mineral phase structure of the full-layer bone cartilage, so that the two regions of the scaffold bone and cartilage of the obtained hydrogel can be well combined together.
[0007] To this end, the first technical solution of the present application discloses a gradient collagen hydroxyapatite conductive hydrogel, which has a double cross-linked network structure, including a primary cross-linked network scaffold formed by collagen, sodium alginate, and polyvinyl alcohol, and a secondary cross-linked network scaffold formed by sodium alginate and metal ions; wherein hydroxyapatite is distributed in a gradient from the bottom of the gel to the top inside the hydrogel scaffold.
[0008] Furthermore, the hydrogel scaffold also includes freely moving metal ions.
[0009] Preferably, the metal ion is Zn 2+ .
[0010] Furthermore, the hydrogel improves mechanical properties through the Hofmeister effect via hydrophilic anions.
[0011] Preferably, the hydrophilic anion is SO4 2- .
[0012] The second technical solution of the present application discloses a method for preparing the above-mentioned gradient collagen hydroxyapatite conductive hydrogel, comprising the following steps:
[0013] S1. uniformly dispersing hydroxyapatite in a collagen solution to obtain a collagen-hydroxyapatite precursor solution;
[0014] S2. adding a mixed solution of sodium alginate and polyvinyl alcohol to the collagen-hydroxyapatite precursor solution, mixing, centrifuging, and freezing to obtain a hydroxyapatite gradient gel;
[0015] S3. The hydroxyapatite gradient gel is immersed in a salt solution composed of metal ions and hydrophilic anions to obtain a gradient collagen hydroxyapatite conductive hydrogel by salting out.
[0016] Furthermore, the addition ratio of the collagen, hydroxyapatite, sodium alginate and polyvinyl alcohol is (10-16):(10-16):(10-16):(3-10); the concentration of the salt solution composed of metal ions and hydrophilic anions is 0.1-2M.
[0017] Furthermore, the centrifugal speed is 3000-10000 rpm, and the centrifugal time is 10-30 min.
[0018] Preferably, the salt solution composed of metal ions and hydrophilic anions is a zinc sulfate solution.
[0019] And, the gradient collagen hydroxyapatite conductive hydrogel prepared according to the above preparation method.
[0020] Beneficial effects of the present invention:
[0021] 1. The present invention uses collagen, sodium alginate, and polyvinyl alcohol (PVA) as primary cross-linked network scaffolds. Sodium alginate is a representative substance among natural polymers and is a linear anionic polysaccharide. Its main chain is distributed with hydrophilic hydroxyl groups and carboxyl groups, which determines the strong hydrophilicity of sodium alginate. However, sodium alginate hydrogel has poor adhesion to cells and is not suitable for bone defect repair. Therefore, collagen has good biocompatibility and low antigenicity, and can promote the attachment and growth of bone marrow mesenchymal stem cells (BMSCs cells), providing a new bone tissue formation. Favorable environment can make up for the poor cell adhesion problem caused by using sodium alginate as hydrogel alone; polyvinyl alcohol can play an auxiliary molding role, which can form various non-covalent bonds, such as hydrogen bonds and crystal domains and hydrophobic interactions, and is often used to construct tough physical hydrogels. PVA chains can also form chain entanglements in the water system under the action of salt ions, making the internal network structure of the hydrogel scaffold more dense and complete; further, sodium alginate and metal ions are used to form a secondary cross-linked network scaffold, which further enhances the stability and mechanical properties of the hydrogel scaffold.
[0022] 2. In the present application, hydroxyapatite is distributed in a gradient inside the hydrogel. It has excellent biocompatibility and osteoinductivity, and has the function of promoting osteogenesis and blood vessel growth. The gradient distribution simulates the process of gradual increase in mineral content during the transition from cartilage to subchondral bone. Compared with the prior art, its structure is more similar to the structure of full-thickness bone cartilage tissue.
[0023] 3. The hydrogel prepared in the present application also contains freely movable metal cations, which provide the gel with conductive properties.
[0024] 4. In the hydrogel preparation process of the present application, hydroxyapatite is first evenly distributed in the collagen solution, and then sodium alginate and polyvinyl alcohol are added to obtain a mixed solution with evenly distributed hydroxyapatite; thereafter, the solution is centrifuged to make the hydroxyapatite particles be distributed in a gradient along the formed hydrogel scaffold, and the transition of the mineral components between the articular cartilage and the subchondral bone is designed to be a continuum, thereby avoiding the traditional method of sequentially implanting multiple layers of hydrogel, which produces a mechanically weak interface between the cartilage layer and the subchondral bone layer. The scaffold that is not centrifuged will cause disorders in the repair process of the two areas of bone and cartilage due to the even distribution of hydroxyapatite. The polymer chemistry and structural continuous gradient are combined so that the two areas of the scaffold bone and cartilage can be well integrated together. After that, the gel polymer is frozen to make it more densely packed, preparing for the strong aggregation and crystallization of the polymer chain caused by subsequent salting out. Then, by introducing a salt solution composed of metal ions and hydrophilic anions, on the one hand, the introduced metal ions can form a cross-linked structure with sodium alginate, and at the same time, some free-moving metal ions will be trapped inside the hydrogel to provide conductivity for the gel. On the other hand, the hydrophilic anions can rapidly improve the mechanical properties of the hydrogel scaffold through the Hofmeister effect and salting out. The resulting hydrogel has both excellent mechanical properties and conductive properties. At the same time, the gradient distribution of hydroxyapatite makes the hydrogel more similar to the full-layer bone cartilage tissue structure, which has better application prospects in bone tissue engineering.
[0025] 5. In the process of preparing the hydrogel of the present application, the salt solution composed of metal ions and hydrophilic anions is preferably zinc sulfate (ZnSO4). On the one hand, the cross-linking effect of zinc ions and sodium alginate can obtain more stable biological properties compared with other metal ions and other cross-linking effects. At the same time, trace amounts of zinc ions can also accelerate bone healing and regulate the physiological activity of osteocytes and osteoclasts, and also have antibacterial effects; on the other hand, SO4 2- The salting-out effect in the Hofmeister effect is the strongest, so zinc sulfate has a more excellent effect on regulating the conductivity and mechanical properties of the hydrogel. In addition, the present invention uses zinc sulfate solution to cross-link the gradient hydrogel, which does not produce substances harmful to the organism and improves the stability and mechanical properties. There are zinc ions Zn chelated with sodium alginate inside the hydrogel. 2+ and free-moving zinc ions Zn 2+ The internal migration of ions gives the hydrogel conductive properties. The prepared gradient collagen-hydroxyapatite conductive hydrogel is completely free of toxic chemicals and has high potential application value in the fields of bioelectrodes and artificial tissue engineering.
[0026] 6. The gradient hydrogel scaffold prepared by the present invention uses a "one-step salt soaking" method to induce a strong salting-out effect, which can change the pore size of the scaffold, form a macroporous structure scaffold, and rapidly improve the mechanical properties. According to different salt types, salt concentrations and soaking times, a multi-level pore structure and different gradient mechanical strengths are generated, which can be better applied in practice.
[0027] 7. The gradient hydrogel scaffold prepared by the present invention uses a "one-step salt soaking" method to induce a strong salting-out effect, which can change the scaffold pore size, form a macroporous structure scaffold, and rapidly improve the mechanical properties. According to different salt types, salt concentrations and soaking time, a multi-level pore structure and different gradient mechanical strengths are generated, which can be better applied in practice. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the gradient collagen-hydroxyapatite conductive hydrogel scaffold prepared in Example 1;
[0029] Figure 2 Nyquist plots of the gradient collagen-hydroxyapatite conductive hydrogel scaffolds prepared in Example 1, Example 2, Example 3, and Example 4;
[0030] Figure 3 The cell activity data of the gradient collagen-hydroxyapatite conductive hydrogel scaffold prepared in Example 3 on BMSCs;
[0031] Figure 4 This is a repair image of the homogeneous uncentrifuged collagen-hydroxyapatite hydrogel scaffold prepared in Example 4 implanted into the knee joint defect of SD mice;
[0032] Figure 5 This is a repair image of the homogeneous uncentrifuged collagen-hydroxyapatite hydrogel scaffold prepared in Example 2 implanted in the knee joint defect of SD mice. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0035] The experimental methods in the following examples are all conventional methods unless otherwise specified. The experimental materials used in the following examples were all purchased from commercial channels, and quality control measures were introduced into the experimental process to ensure the quality of the data results.
[0036] The first embodiment of the present application discloses a gradient collagen hydroxyapatite conductive hydrogel, which has a double cross-linked network structure, including a primary cross-linked network scaffold formed by collagen, sodium alginate, and polyvinyl alcohol, and a secondary cross-linked network scaffold formed by sodium alginate and metal ions; wherein hydroxyapatite is distributed in a gradient from the bottom of the gel to the top inside the hydrogel scaffold.
[0037] In the cartilage structure, the mineral content gradually increases during the transition from cartilage to subchondral bone. At the same time, since it is used to repair bone injuries, the hydrogel is required to have a certain mechanical strength. Although the currently commonly used uniform structure hydrogels have mechanical properties, they may cause disorder in the repair process and make it difficult to form a bone cartilage structure similar to the native tissue; and the method of implanting multiple hydrogels in sequence may lead to weak interface bonding and unstable mechanical properties; and the integrated multiphase bone cartilage repair hydrogel in the prior art cannot simulate the process of gradual increase in mineral content; based on this, the gradient collagen hydroxyapatite conductive hydrogel provided in the present application provides excellent mechanical properties through a double cross-linked network structure. At the same time, hydroxyapatite is distributed in a gradient from the bottom of the adjacent corner to the top, simulating the process of gradual increase in mineral content in cartilage, so that the gel has both biological and mechanical properties.
[0038] It can be understood that in this embodiment, the metal ions are metal cations that can be cross-linked with sodium alginate and are harmless to the human body, such as divalent magnesium ions, divalent zinc ions, etc., which enhance the mechanical properties of the gel by chelating with sodium alginate.
[0039] In this embodiment, the hydroxyapatite is preferably synthesized by a hydrothermal method, and its synthesis method is specifically as follows: prepare raw materials Ca(OH)2 (250 mesh-160 mesh) and H3PO4, weigh 3.70g Ca(OH)2 and dissolve it in 200ml RO water, and stir it in a closed manner at room temperature for 2h to form a uniform suspension (add 1ml polyethylene glycol 400 during this period); prepare 100ml of 0.3M H3PO4 solution, and slowly drip it into the above solution, controlling the dripping rate: 2 drops / second (keeping the solution continuously stirred); after the dropwise addition is completed, continue stirring at room temperature for 4h, then stop stirring and age for 24h (keep sealed); after the aging is completed, discard the supernatant, take part of the lower layer liquid in an EP tube for standby use, repeatedly centrifuge and wash twice with anhydrous ethanol and RO water, after drying, sinter in a muffle furnace at 5℃ / min, 1150℃ for 2h to improve the crystallinity of hydroxyapatite. The hydroxyapatite prepared by this method has excellent biocompatibility and osteoinductivity, and is an extremely important material for bone tissue engineering. Hydroxyapatite has the function of promoting osteogenesis and blood vessel growth, and is mainly used for repairing hard bone parts. At the same time, hydroxyapatite as an inorganic mineral provides a certain degree of mechanical strength for the hydrogel.
[0040] In a further embodiment, the hydrogel scaffold further includes freely moving metal ions. It is understood that the metal ions are introduced during the chelation process between sodium alginate and the metal ions, and their freely moving characteristics provide the hydrogel with conductive properties, which can stimulate cell activity.
[0041] In a further embodiment, since the hydrogel is a protein-based (collagen) gel, the applicant also introduces hydrophilic anions based on the Hofmeister effect to further improve the mechanical properties of the hydrogel through salting out, and the preferred anions are sulfate ions.
[0042] In the above hydrogel, the mass ratio of collagen, sodium alginate, polyvinyl alcohol and hydroxyapatite is:
[0043] The second embodiment of the present application discloses a method for preparing the above-mentioned gradient collagen hydroxyapatite conductive gel, comprising:
[0044] S1. uniformly dispersing hydroxyapatite in a collagen solution to obtain a collagen-hydroxyapatite precursor solution;
[0045] S2. adding a mixed solution of sodium alginate and polyvinyl alcohol to the collagen-hydroxyapatite precursor solution, mixing, centrifuging, and freezing to obtain a hydroxyapatite gradient gel;
[0046] S3. The hydroxyapatite gradient gel is immersed in a salt solution composed of metal ions and hydrophilic anions to obtain a gradient collagen hydroxyapatite conductive hydrogel by salting out.
[0047] In a specific embodiment, since the collagen solution is weakly acidic and hydroxyapatite is alkaline, hydroxyapatite is first evenly dispersed in the collagen solution. The reason is that the pH can be neutralized to 6.5-7, which is similar to the pH value of the human body. Polyvinyl alcohol and sodium alginate have certain gelling and sealing properties. It is necessary to ensure that hydroxyapatite is evenly mixed in the collagen before adding polyvinyl alcohol and sodium alginate to form the solution.
[0048] It can be understood that in order to facilitate uniform mixing, the collagen, sodium alginate and polyvinyl alcohol are mixed in the form of solutions, wherein the concentration range of the collagen solution is preferably 7.9-13 mg / g, the sodium alginate solution needs to be heated to dissolve, and the concentration range of the sodium alginate and PVA solutions is 26-87 mg / mL.
[0049] It can be understood that in the prepared mixed solution, hydroxyapatite is evenly dispersed, and then centrifuged to make hydroxyapatite dispersed in the gel in a gradient; on the other hand, centrifugation can also design different tissues into a continuum, avoiding the mechanical weak interface between different layers, so that the resulting hydrogel can be well integrated with cartilage and has both mechanical and biological properties. In a preferred embodiment, the centrifugal speed is 3000-10000rpm, and the centrifugal time is 10-30min.
[0050] In order to further improve the mechanical and biological properties, the hydrogel prepared in the above steps is frozen and then immersed in a salt solution composed of metal ions and hydrophilic anions for salting out. In this process, a part of the metal ions can chelate with sodium alginate to form a second-level cross-linked network, and a part of the free-moving metal ions will be trapped in the gel scaffold to provide the hydrogel with conductive properties; the hydrophilic anions can cause the protein-based hydrogel to undergo the Hofmeister effect, further improving the mechanical properties of the hydrogel. In a preferred embodiment, the salt solution is a zinc sulfate solution with a concentration of 0.1-2M.
[0051] The hydrogel prepared by the above method has a double cross-linked network structure, including a primary cross-linked network scaffold formed by collagen, sodium alginate, and polyvinyl alcohol, and a secondary cross-linked network scaffold formed by sodium alginate and metal ions; at the same time, hydroxyapatite is distributed in a gradient from the bottom of the gel to the top inside the hydrogel scaffold, and the gel also includes freely movable metal ions; so that the gel has both mechanical properties and biological properties.
[0052] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0053] Example 1
[0054] Weigh 3.70g Ca(OH)2 (250-160 mesh) and dissolve it in 200ml RO water. Stir it in a closed container at room temperature for 2h to form a uniform suspension (add 1ml polyethylene glycol 400 during this period); prepare 100ml of 0.3M H3PO4 solution and slowly drip it into the above solution, controlling the dripping rate to 2 drops / second; after the addition is completed, continue stirring at room temperature for 4h, age for 24h, discard the supernatant, take part of the lower layer of liquid in an EP tube for later use, repeatedly centrifuge and wash twice with anhydrous ethanol and RO water, after drying, sinter in a muffle furnace for 2h (5℃ / min, 1150℃) to improve the crystallinity of hydroxyapatite, and then grind for use.
[0055] Weigh 10g of 13mg / g collagen solution and place it in a container, then weigh 65mg of ground hydroxyapatite powder, add it to the collagen solution in small amounts and multiple times, keep it sealed at 4℃ and stir it for 10h to make the hydroxyapatite evenly dispersed; then weigh 130mg of sodium alginate powder, add 1.5ml of deionized water and dissolve it in an 85℃ water bath for about 25min, after the sodium alginate is fully dissolved, add 39mg of polyvinyl alcohol (PVA) and continue to stir and dissolve for 25min; add collagen-hydroxyapatite precursor solution and stir at low speed for 30min to mix evenly; divide it into 1.5ml centrifuge tubes, centrifuge it at 8000rpm for 10min, place the centrifuged solution in a -20℃ refrigerator and freeze it for 10h until it is completely frozen, take out the materials and soak them in 0.1M ZnSO4 solution for 10h to obtain a conductive hydrogel with hydroxyapatite as the mineral gradient, which is used for the repair of the junction of articular cartilage and subchondral bone.
[0056] Example 2
[0057] Weigh 3.70g Ca(OH)2 (250-160 mesh) and dissolve it in 200ml RO water. Stir it in a closed container at room temperature for 2h to form a uniform suspension (add 1ml polyethylene glycol 400 during this period); prepare 100ml of 0.3M H3PO4 solution and slowly drip it into the above solution, controlling the dripping rate to 2 drops / second; after the addition is completed, continue stirring at room temperature for 4h, age for 24h, discard the supernatant, take part of the lower layer of liquid in an EP tube for later use, repeatedly centrifuge and wash twice with anhydrous ethanol and RO water, after drying, sinter in a muffle furnace for 2h (5℃ / min, 1150℃) to improve the crystallinity of hydroxyapatite, and then grind for use.
[0058] Weigh 10g 13mg / g collagen solution is placed in a container, and then 65mg of ground hydroxyapatite powder is weighed and added to the collagen solution in small amounts and multiple times, and the mixture is kept sealed at 4℃ and stirred for 10 to make the hydroxyapatite evenly dispersed; then 130mg of sodium alginate powder is weighed, 1.5ml of deionized water as little as possible is added and dissolved in an 85℃ water bath for about 25min, and after the sodium alginate is fully dissolved, 39mg of polyvinyl alcohol (PVA) is added and continued to be stirred and dissolved for 25min; after the above solution is fully dissolved, the temperature drops below 37℃, and the pre-configured collagen-hydroxyapatite precursor solution is added, and the mixture is stirred at a low speed for 30min to mix evenly; the mixture is divided into 1.5ml centrifuge tubes, centrifuged at 8000rpm for 10min, and the solution after centrifugation is placed in a -20℃ refrigerator for 10h until it is completely frozen, and the materials are taken out and soaked in 0.5M ZnSO4 solution for 10h to obtain a conductive hydrogel with hydroxyapatite as the mineral gradient, which is used for the repair of the junction of articular cartilage and subchondral bone.
[0059] Example 3
[0060] Weigh 3.70g Ca(OH)2 (250-160 mesh) and dissolve it in 200ml RO water. Stir it in a closed container at room temperature for 2h to form a uniform suspension (add 1ml polyethylene glycol 400 during this period); prepare 100ml of 0.3M H3PO4 solution and slowly drip it into the above solution, controlling the dripping rate to 2 drops / second; after the addition is completed, continue stirring at room temperature for 4h, age for 24h, discard the supernatant, take part of the lower layer of liquid in an EP tube for later use, repeatedly centrifuge and wash twice with anhydrous ethanol and RO water, after drying, sinter in a muffle furnace for 2h (5℃ / min, 1150℃) to improve the crystallinity of hydroxyapatite, and then grind for use.
[0061] Weigh 10g 13mg / g collagen solution is placed in a container, and then 65mg of ground hydroxyapatite powder is weighed and added to the collagen solution in small amounts and multiple times, and the mixture is kept sealed at 4℃ and stirred for 10-24h to make the hydroxyapatite evenly dispersed; then 130mg of sodium alginate powder is weighed, 1.5ml of deionized water as little as possible is added and dissolved in an 85℃ water bath for about 25min, and after the sodium alginate is fully dissolved, 39mg of polyvinyl alcohol (PVA) is added and continued to be stirred and dissolved for 25min; after the above solution is fully dissolved, the temperature drops below 37℃, and the pre-configured collagen-hydroxyapatite precursor solution is added, and the mixture is stirred at low speed for 30min to mix evenly; the mixture is divided into 1.5ml centrifuge tubes, centrifuged at 8000rpm for 10min, and the solution after centrifugation is placed in a -20℃ refrigerator for 10h until it is completely frozen, and the materials are taken out and soaked in 1M ZnSO4 solution for 10h to obtain a conductive hydrogel with hydroxyapatite as the mineral gradient, which is used for the repair of the junction of articular cartilage and subchondral bone.
[0062] Example 4
[0063] Weigh 3.70g Ca(OH)2 (250-160 mesh) and dissolve it in 200ml RO water. Stir it in a closed container at room temperature for 2h to form a uniform suspension (add 1ml polyethylene glycol 400 during this period); prepare 100ml of 0.3M H3PO4 solution and slowly drip it into the above solution, controlling the dripping rate to 2 drops / second; after the addition is completed, continue stirring at room temperature for 4h, age for 24h, discard the supernatant, take part of the lower layer of liquid in an EP tube for later use, repeatedly centrifuge and wash twice with anhydrous ethanol and RO water, after drying, sinter in a muffle furnace for 2h (5℃ / min, 1150℃) to improve the crystallinity of hydroxyapatite A, and then grind for use.
[0064] Weigh 10g of 13mg / g collagen solution and place it in a container, then weigh 65mg of ground hydroxyapatite powder, add it to the collagen solution in small amounts and multiple times, keep it sealed at 4℃ and stir it for 10h to make the hydroxyapatite evenly dispersed; then weigh 130mg of sodium alginate powder, add as little deionized water as possible 1.5ml and dissolve it in an 85℃ water bath for about 25min, after the sodium alginate is fully dissolved, add 39mg of polyvinyl alcohol (PVA) and continue to stir and dissolve for 25min; after the above solution is fully dissolved, the temperature drops below 37℃, add the pre-configured collagen-hydroxyapatite precursor solution, and stir at low speed for 30min to mix evenly; divide the mold, then place it in a -20℃ refrigerator to freeze for 10h until it is completely frozen, take out the materials and soak them in 0.5M ZnSO4 solution for 10h to obtain collagen-hydroxyapatite homogeneous conductive hydrogel for comparison.
[0065] Compared with Example 2, Example 4 is not subjected to centrifugation.
[0066] like Figure 1 Shown is a SEM image of a gradient collagen-hydroxyapatite conductive hydrogel scaffold. It can be seen from the figure that the hydrogel prepared in Example 1 has a structure in which the hydroxyapatite content is gradiently distributed from high to low from the bottom of the gel upward, and retains a certain pore structure that is conducive to cell migration and adhesion.
[0067] like Figure 2 The Nyquist curves of the gradient collagen-hydroxyapatite conductive hydrogel scaffolds prepared in Example 1, Example 2, Example 3, and Example 4 are shown. Figure 2 It can be seen that within a certain concentration range of zinc sulfate solution, the conductivity of the hydrogel increases with the increase of the salt solution concentration.
[0068] like Figure 3Shown are the stress-strain curves of the homogeneous uncentrifuged collagen-hydroxyapatite hydrogel scaffolds prepared in Example 4 and Example 2 (test speed 5 mm / min). It can be seen from the figure that the homogeneous uncentrifuged hydrogel scaffold can withstand greater stress due to the uniform distribution of hydroxyapatite inside it, and the centrifuged gradient collagen-hydroxyapatite conductive hydrogel scaffold has hydroxyapatite concentrated at one end, so the stress it is subjected to is weaker than that of the homogeneous uncentrifuged group and has better ductility.
[0069] like Figure 4 The figure shows the macroscopic repair condition of the homogeneous uncentrifuged collagen-hydroxyapatite hydrogel scaffold prepared in Example 4 implanted in the knee joint defect of SD mice (hole diameter 3 mm, depth 3.5 mm) for 4 weeks. It can be seen from the figure that there is still an obvious depression on the surface of the knee joint four weeks after the homogeneous hydrogel scaffold is implanted.
[0070] like Figure 5 The figure shows the macroscopic repair of the gradient collagen-hydroxyapatite hydrogel scaffold prepared in Example 1 implanted in the knee joint defect of SD mice (pore diameter 3 mm, depth 3.5 mm) for 4 weeks. It can be seen from the figure that the knee joint is basically repaired four weeks after the gradient hydrogel scaffold is implanted, the joint surface is flat, and there is obvious new bone formation in the original pore defect area.
[0071] The above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. The embodiments of the present invention and the features in the embodiments can be arbitrarily combined with each other without conflict. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A gradient collagen hydroxyapatite conductive hydrogel, characterized in that: The hydrogel is a double cross-linked network structure, including a primary cross-linked network scaffold formed by collagen, sodium alginate, and polyvinyl alcohol, and a secondary cross-linked network scaffold formed by sodium alginate and metal ions; wherein the hydroxyapatite content is distributed in a gradient from high to low inside the hydrogel scaffold from the bottom of the gel upward.
2. The gradient collagen hydroxyapatite conductive hydrogel according to claim 1, characterized in that: The hydrogel scaffold also includes freely moving metal ions.
3. The gradient collagen hydroxyapatite conductive hydrogel according to claim 1 or 2, characterized in that: The metal ion is Zn 2+ Mg 2+ .
4. The gradient collagen hydroxyapatite conductive hydrogel according to claim 1, characterized in that: The hydrogel improves mechanical properties through ion-specific effects using hydrophilic anions.
5. The gradient collagen hydroxyapatite conductive hydrogel according to claim 4, characterized in that: The hydrophilic anion is SO4 2- 、S2O3 2- .
6. The method for preparing the gradient collagen hydroxyapatite conductive hydrogel according to any one of claims 1 to 5, characterized in that: The steps include: S1. uniformly dispersing hydroxyapatite in a collagen solution to obtain a collagen-hydroxyapatite precursor solution; S2. adding a mixed solution of sodium alginate and polyvinyl alcohol to the collagen-hydroxyapatite precursor solution, mixing, centrifuging, and freezing to obtain a hydroxyapatite gradient gel; S3. The hydroxyapatite gradient gel is immersed in a salt solution composed of metal ions and hydrophilic anions to obtain a gradient collagen hydroxyapatite conductive hydrogel by salting out.
7. The preparation method according to claim 6, characterized in that: The added amounts of the collagen, hydroxyapatite, sodium alginate and polyvinyl alcohol are (10-16):(10-16):(10-16):(3-10); the concentration of the salt solution composed of metal ions and hydrophilic anions is 0.1-1M.
8. The preparation method according to claim 6, characterized in that: The centrifugal speed is 3000-10000rpm, and the centrifugal time is 10-30min.
9. The preparation method according to claim 6, characterized in that: The salt solution composed of metal ions and hydrophilic anions is a zinc sulfate solution.
10. The gradient collagen hydroxyapatite conductive hydrogel prepared according to any one of the preparation methods of claims 6-9.
Citation Information
Patent Citations
High-strength hydrogel based on three-dimensional network support and preparation method of high-strength hydrogel
CN108525018A
Method of preparing self-driving gradient-composition hydrogel through supergravity and application of the hydrogel
CN109280183A
Cartilage repair membrane and preparation method thereof
CN116688231A
Mineralized hydrogel based on biomineralization and salting-out effects as well as preparation method and application of mineralized hydrogel
CN118685046A
Compositions, implants, methods, and kits for closure of lumen openings, repair of ruptured tissue, and for bulking of tissue
US20020176893A1